Nonstereoselective foliar absorption and translocation of cycloxaprid, a novel chiral neonicotinoid, in Chinese cabbage. (September 2019) - Cheng, Xi; Wang, Yichen; Li, Wei; Li, Qinkan; Luo, Peiwen; Ye, Qingfu
Abstract: Exploring traditional neonicotinoid pesticides substitutes has become one of the global scientific attentions because of their hazardous environmental impacts. Cycloxaprid (CYC) is considered to be a promising candidate alternative. But the environmental behaviors and fate of CYC in different planting system remain poorly understood. The accumulation of 14 C-labeled CYC stereoisomers within different parts of Chinese cabbage ( Brassica chinensis L.) was investigated, with a particular focus on the foliar absorption, translocation and stereoselectivity of CYC, during a laboratory trial. In general, the stereoisomers 14 C-5R, 8S-CYC and 14 C-5S, 8R-CYC, their metabolites, as well as the breakdown and reaction products can be transferred in both acropetal and basipetal directions. Most of the two stereoisomers absorbed by plants remained in the treated leaves, whereas a small amount was distributed to the roots. The amount of 14 C in the stalks varied among the experimental time points. At 192 h after treatment (HAT), the detected radioactivity of both 14 C-5R, 8S-CYC and 14 C-5S, 8R-CYC in the leaves above the treated leaf (LATL) was higher than that in the leaves below the treated leaf (LBTL). However, the stereoisomers of CYC underwent nonstereoselective absorption and translocation in this trial. This information implies that racemic CYC and its metabolites should be a main research focus. Thus, the obtained results provide implications for a more accurate prediction about the risk assessment of CYC, which will be helpful for guiding its rational use as well as securing the ecological environment safety and human health. Graphical abstract: Image 10925 Highlights: Most of the two cycloxaprid stereoisomers absorbed by plants remained in the treated leaves. Only a small amount was transported to the roots. The detected radioactivity of both stereoisomers in the LATL was higher than that in the LBTL. No significant difference in distribution was detected between the two stereoisomers. Abstract : The stereoisomers of 14 C-labeled CYC underwent nonstereoselective absorption and translocation in Chinese cabbage.